MAKNA AKUNTANSI DALAM PERSPEKTIF PEDAGANG BAKSO “AREMA” PERANTAUAN DI KOTA GORONTALO - Wiji Lestari Suwanto; Niswatin .; La ode Rasuli (Universitas Negeri Malang, 2016)
Abstract:The aim of this research is to find an to describe the meaning of accountancy in perspective ofthe Bakso Arema seller. This research is focusing on Bakso Arema sellers who moved from their home-town to Gorontalo. The data for this research was collected through observation, interview and picturedocumentation. This research is conducted qualitatively by using interpretive paradigm and symbolicinteractionism as a method and tool of analysis and the analysis unit is focusing on mind, self andsociety of analyzed object. The meaning of accountancy is really interesting from the perspective ofBakso Arema sellers, because they are doing a complete report of their business which is considered asaccountancy. The result of this research showed that in their business activity the Bakso Arema sellersmeasured accountancy by way of; (1) accountancy as an information (2) accountancy as a responsibil-ity (3) accountancy as a calculation (base of decision)Keywords:accountancy, meaning, bakso sellers